Philosophy and Ataraxia in Sextus Empiricus - Massie, Pascal (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2013)
This essay addresses two interconnected questions: (a) In what sense is Skepticism a philosophy? (b) How can ataraxia emerge out of epochē? Skepticism is a practice that articulates three moments: equipollence, epochē (suspension of judgment), and ataraxia (freedom from disturbance) and Sextus’ account of how one can move through these moments demonstrates the its philosophical nature. However, to clarify the transition from epochē to ataraxia Sextus offers only one clue: the story of Apelles. If this story is paradigmatic, it is also ambiguous since the transition from epochē to ataraxia can neither be causal nor inferential. Apelles achieves his goal purely by chance. Contrary to a common interpretation, this doesn’t mean that the Skeptic abandons the inquiry (just as Apelles doesn’t abandon painting). Lastly, the essay argues that Skepticism is not only the practice of a certain dialectical method but also a practice upon oneself. The Skeptic must learn to dissociate herself from the thoughts she entertains. Sustained inquiry can coexist with ataraxia because the Skeptic has discovered that her consciousness is distinct from its intentional content now bracketed by epochē. To free ourselves from our attachment to dogmatic beliefs is to opens up a space of self-detachment.
Keywords: Skepticism; Sextus Empiricus